Multifunctional microspherical magnetic and pH responsive carriers for combination anticancer therapy engineered by droplet-based microfluidics. Issue 22 (16th May 2017) - Maher, Shaheer; Santos, Abel; Kumeria, Tushar; Kaur, Gagandeep; Lambert, Martin; Forward, Peter; Evdokiou, Andreas; Losic, Dusan
Abstract : Drug loaded luminescent porous silicon diatoms and magnetic bacterial nanowires were encapsulated within pH sensitive polymer forming biodegradable microcapsules using droplet-based microfluidics for targeting colorectal cancer. Abstract : pH stimuli responsive drug delivery platforms that can target specific locations along the gastrointestinal tract hold great promise for colorectal cancer therapy. Herein, we present a facile approach to produce microfluidic engineered pH-sensitive magnetic microspherical carriers containing multifunctional therapeutic payloads for synergistic treatment of colorectal cancer. Chemotherapeutics, 5 fluorouracil (5FU) and curcumin (CUR), were chosen due to their synergistic effect for colorectal cancer treatment and prevention. Drugs were loaded onto naturally derived porous silicon nanoparticles (SiNPs) and magnetic bacterial iron oxide nanowires (BacNWs), which acted as drug nanocontainers and magnetic elements, respectively. Drug loaded SiNPs and BacNWs were then encapsulated into polymeric microspheres using droplet-based microfluidics. To ensure controlled drug delivery into the desired site of action (colon and rectum), the microspheres were fabricated using hypromellose acetate succinate polymers, which are insoluble in the acidic medium of the stomach ( i.e. pH 1.2) but soluble at basic pH (colon and rectum). Our results confirmed that the microspheres exhibit a narrow size distribution (CV > 5%) with precise size control. Moreover, in vitro dissolution and drug release data confirmed their pH-responsive properties. Motivated by these results, we explored the biocompatibility of microspheres using human RAW 264.7 macrophages. The results revealed the safety of drug free microspheres up to 1000 μg mL −1 . Finally, the synergistic action of 5FU and CUR loaded microspheres was investigated on SW480 colon adenocarcinoma cells.